(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the special genre of "history" in the English literature of the 19th century, the originality of which is manifested in the integration of history and literature. Analyzes the "history" W. Scott («Tales of a Grandfather being the History of Scotland from earliest period to the Battle of Flodden in 1513»), Charles Dickens («A Childs history of England») and William Thackeray («Miss Tickletoby`s Lectures on English History». «The History of the Next French Revolution»). Art concept known writers is mapped to the concept of English historians T. Carlyle, J. Mill, T. Macaulay. The conclusion is made that Scott and Dickens create a fictional story, and Thackeray – a parody of the genre of historiography. The relevance of the article is connected with the increased interest in the problems of national identity and national myth, national image, and other. Materials Presented can be used in the course "Children’s literature" and "History of foreign literature of the XIX century".